OP44 Trends in Community Violence in England and Wales 2005-2009. (10th September 2013) - Sivarajasingam, V; Page, N A; Morgan, P; Matthews, K; Moore, S; Shepherd, J P
Abstract : Background: Recognising the need for clarity in national violence trends, injury records from Emergency Departments (EDs) have been studied over the last decade as part of the work of the National Violence Surveillance Network (NVSN) and provide information about local, regional and national violence levels and trends in England and Wales. The purpose of the current study is to evaluate overall, gender, age-specific and regional trends in community violence in England and Wales from an ED perspective for the period 2005-2009. Methods: Violence-related injury data were collected prospectively in a stratified sample of 77 EDs (Types 1, 3 and 4) in the nine Government Office Regions in England and in Wales over five years, January 1 2005 to 31st December 2009. Attendance date, age and gender of patients who reported injury in violence were studied. Time series statistical methods were used to detect national trends. Results: In total 221, 673 (163, 384 males: 74%) violence-related attendances were identified. Overall estimated annual injury rate was 6.5 per 1000 resident population (9.8 and 3.4 for males and females respectively). Violence affecting males and females decreased significantly in England and Wales over the five year period (p < 0.05), with an overall estimated annual decrease of 2.4%. Attendances for those aged 17 years and under and those aged 31 years and over decreased significantly (p < 0.05), however violence affecting those aged 18-30 years did not change. There were significant regional differences in violence-related ED attendances with decreases in Eastern, North East, North West, South East Regions and Wales and increases in East Midlands, London, South West and West Midlands regions (p < 0.05). Regarding seasonal differences, violence-related ED attendances were highest during the months of May and July and lowest in February. Conclusion: From this ED perspective overall violence in England and Wales decreased over the period 2005-2009 but increased in the East Midlands, London, South West and West Midlands. Since 2006, overall trends according to the Crime Survey for England and Wales (CSEW), police and ED measures were similar, though CSEW and ED measures reflect far greater numbers of violent incidents than police data. Causes of decreases in some regions need to be identified, shared and solutions implemented within regions where violence increased. Violence prevention efforts should also be extended so that the December drink driving and safety campaigns are implemented in the period May – July.